Redes automotivas: análise teórica e experimental - Flores, Matheus Falleiros de Almeida Valladão (Universidade Federal de São Carlos, 2017)
Every year new items of comfort, safety and technology are added to the vehicles. In Brazil, for example, it is already law that any national vehicle has ABS (Antiblockier-Bremssystem) and Airbag brakes. These systems require elaborate electronic systems and the connection of several sensors, typically in a network. In addition, most vehicles currently sold have one or more communication networks. In particular, the use of the network increases the reliability, flexibility of the designs and also reduces costs and the final weight of the vehicle with the reduction of cables. Knowing that automotive CAN (Controller Area Network) networks can be accessed via the OBD-II Board Diagnostics), allowing access to the codes and their analysis, proposes the study of vehicle network technologies, through theoretical study, experimental analysis and analysis of commercial tools. To this end, the objective is first to compare commercial tools and then to build a device for data analysis. This device will consist of a microcontroller that is connected to a CAN controller and a CAN transciever to physically couple the electrical signals from the CAN controller to the network, with bidirectional capabilities and data direction control. This device will be used to collect data from vehicles for further analysis. It is hoped, therefore, to develop tools and knowledge for the analysis and performance in automotive CAN networks, comparing the commercial tools available, and thus, giving more subsidies for future research, teaching and developments in the area.
Automotive networks: theoretical and experimental analysis
Keywords: CAN Automotivo; OBD; Análise de Protocolo; Análise experimental; ENGENHARIAS::ENGENHARIA MECANICA::PROJETOS DE MAQUINAS